2015
DOI: 10.1093/jsh/shu149
|View full text |Cite
|
Sign up to set email alerts
|

An Agro-Town Bias? Re-examining the Micro-Demographic Model for Southern Italy in the Eighteenth Century

Abstract: Over the past 25 years, there has been an orthodox view established that 18thcentury Southern Italy had a distinctive micro-demographic model based around a number of facets, 3 key ones being a proliferation of neo-local small nuclear households, an exceptionally low average age of first marriage for women (with low levels of life-time singles), and a low incidence of household service. This view, however, has been forged on the back of geographical biases in data selectionparticularly in favor of Apulia, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…However, we have good reasons to expect that filling this gapif doing so is ever possiblewould only strengthen our results, as at least the Italian sub-regional variation in household formation patterns would not reveal a specific distinct monolith-like cluster within our data structure, but would instead be partitioned between the existing cluster structure that we have derived. Nevertheless, further research including Italy might prove useful, given that part of its suggested micro-demographic variability has recently been claimed to have been forged on the back of geographical biases in data selection (Curtis 2015). As for now, however, our results confirm that the claim made about Italy-i.e., that it is "a burial ground for many of the most ambitious and well-known theories of household and marriage systems" (Kertzer 1991b, 247) may have wider pan-European implications, and cannot be dismissed as a mere peculiarity of the Mediterranean.…”
Section: Discussionsupporting
confidence: 74%
“…However, we have good reasons to expect that filling this gapif doing so is ever possiblewould only strengthen our results, as at least the Italian sub-regional variation in household formation patterns would not reveal a specific distinct monolith-like cluster within our data structure, but would instead be partitioned between the existing cluster structure that we have derived. Nevertheless, further research including Italy might prove useful, given that part of its suggested micro-demographic variability has recently been claimed to have been forged on the back of geographical biases in data selection (Curtis 2015). As for now, however, our results confirm that the claim made about Italy-i.e., that it is "a burial ground for many of the most ambitious and well-known theories of household and marriage systems" (Kertzer 1991b, 247) may have wider pan-European implications, and cannot be dismissed as a mere peculiarity of the Mediterranean.…”
Section: Discussionsupporting
confidence: 74%